2002
DOI: 10.1128/aem.68.6.2885-2892.2002
|View full text |Cite
|
Sign up to set email alerts
|

Dothistroma pini , a Forest Pathogen, Contains Homologs of Aflatoxin Biosynthetic Pathway Genes

Abstract: Homologs of aflatoxin biosynthetic genes have been identified in the pine needle pathogen Dothistroma pini. D. pini produces dothistromin, a difuranoanthraquinone toxin with structural similarity to the aflatoxin precursor versicolorin B. Previous studies with purified dothistromin suggest a possible role for this toxin in pathogenicity. By using an aflatoxin gene as a hybridization probe, a genomic D. pini clone was identified that contained four dot genes with similarity to genes in aflatoxin and sterigmatoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 49 publications
2
56
0
1
Order By: Relevance
“…In a third example, Dothistroma pini makes dothistromin with products of genes that are orthologous to those of the aflatoxin biosynthetic pathway found in Aspergillus spp. (48).…”
Section: Diversification Of Pks Genes Among Species In the Pezizomycomentioning
confidence: 99%
“…In a third example, Dothistroma pini makes dothistromin with products of genes that are orthologous to those of the aflatoxin biosynthetic pathway found in Aspergillus spp. (48).…”
Section: Diversification Of Pks Genes Among Species In the Pezizomycomentioning
confidence: 99%
“…They encode proteins with unknown functions and probably are not necessary for ST biosynthesis. A homolog to stcC is found in the dothistromin biosynthetic cluster (Bradshaw, Bhatnagar et al 2002). Another gene loss appears to have occurred relatively recently, perhaps within the last 1 million years.…”
Section: Evolution Of the Aflatoxin Gene Clustermentioning
confidence: 99%
“…The genes for AF/ST/dothistromin synthesis have been retained for greater than 125 million years and it is probable that the polyketides encoded by these clusters enabled the fungi to survive and prosper as free-living organisms in diverse environments (Bradshaw, Bhatnagar et al 2002;Gomez and Nosanchuk 2003). We assume that the reason for maintaining such gene clusters is that the precursor metabolites are critical for fungal adaptation.…”
Section: Evolution Of the Aflatoxin Gene Clustermentioning
confidence: 99%
“…Ferguson et al (1986) have shown that the toxin causes chromosome abnormalities in human lymphocytes and Skinnider et al (1989) found an increase in frequency of sister chromatid exchange. Also of interest is that the biosynthetic pathway leading to the production of dothistromin is very similar to the pathway that leads to aflatoxin production, a human carcinogen (Bradshaw et al 2002). Studies on the toxin are important both for developing methods of control of this pathogen, but also for the development of safety protocols for forest workers.…”
Section: Health Hazardsmentioning
confidence: 99%
“…Worker exposure to toxin was greater in wet conditions versus dry and was also affected by season and environment (Elliott et al 1989). The increasing incidence of Dothistroma disease epidemics in the Northern hemisphere is also of concern (Bradshaw et al 2002). An understanding of risks is essential for development of safety protocols for forest workers.…”
Section: Health Hazardsmentioning
confidence: 99%